Medi-Block record: Secure data sharing using block chain technology - Singh, Chaitanya; Chauhan, Deepika; Deshmukh, Sushama A.; Vishnu, Swati Sudhakar; Walia, Ranjan (Informatics in medicine unlocked, 2021)
With the advances in the era of Artificial intelligence, block chain, cloud computing, big data has the need for secure, decentralized medical record storage and retrieval systems, while cloud storage resolves storage issues but it is difficult to realize the secure sharing of records over the network. The decentralized nature of block chain technology resolves the problem of authentication dependent on third party and imparts secure transmission. This paper proposed block chain based distributed authentication mechanism process and network architecture. Medi-Block presents a tamperproof and anonymous identity management model for medical record sharing for hospitals and patients, utilizing the concept of bilinear mapping for the authentication phase and eliminating third party trust issues. It implements two-way authentications between the patients and the hospital. The effectiveness of the proposed authentication scheme is analyzed by BAN logic, storage overhead and computing cost. The results presented in the paper demonstrate how a block chain platform based on BAN logic can enable medical data sharing while also meeting various security requirements during the authentication phase. Furthermore, reducing average communication time and cost in terms of accessibility meets the requirements of medical data record sharing for integrity, privacy, and availability.